2012
DOI: 10.1007/s12098-012-0869-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oil Massage on Growth in Preterm Neonates Less than 1800 g: A Randomized Control Trial

Abstract: Oil application has a potential to improve weight gain and cause less weight loss in first 7 d in low birth weight neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 4 publications
3
32
0
5
Order By: Relevance
“…The outcome most commonly assessed on randomized controlled trials of massage in preterm infants (Table 1) was weight gain, either as primary or secondary outcome [2,5,8,9,10,12,15,16,17,18,19,21,26,28,29,30,31,33,34,35]. Other outcomes assessed in RCTs of massage in preterm infants include levels of transcutaneous bilirubin [3], sleep [4,26], calorie intake [5,17,19,30,33,34,35], vagal activity [5,19,24,26,29,30], gastric motility or number of stools [3,24,30], heart rate variability (HRV) [6,7,19,24,30], immunologic parameters [12], bone metabolism [11,32], changes in electroencephalogram (EEG) [13], behavior and/or neurodevelopment [14,15,23,26,28,29,31,34,35], pain [25], length of hospital stay [12,16,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcome most commonly assessed on randomized controlled trials of massage in preterm infants (Table 1) was weight gain, either as primary or secondary outcome [2,5,8,9,10,12,15,16,17,18,19,21,26,28,29,30,31,33,34,35]. Other outcomes assessed in RCTs of massage in preterm infants include levels of transcutaneous bilirubin [3], sleep [4,26], calorie intake [5,17,19,30,33,34,35], vagal activity [5,19,24,26,29,30], gastric motility or number of stools [3,24,30], heart rate variability (HRV) [6,7,19,24,30], immunologic parameters [12], bone metabolism [11,32], changes in electroencephalogram (EEG) [13], behavior and/or neurodevelopment [14,15,23,26,28,29,31,34,35], pain [25], length of hospital stay [12,16,…”
Section: Resultsmentioning
confidence: 99%
“…Studies assessing the effects of massage on caregivers only were excluded. A total of 34 randomized controlled trials on the effects of massage in preterm infants are reviewed [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35]. …”
Section: Introductionmentioning
confidence: 99%
“…Evidence supporting positive effects of massage in preterm infants include increased weight gain [1820], improved growth and gastrointestinal function [21, 22], improved body fat deposition [23], improved neurobehavioural outcomes [17, 2426], pain attenuation [27, 28], reduction of infant stress and stress-related factors [29, 30], reduction of late-onset sepsis [31], improved immune system [32], reduced jaundice [33] and improved heart rate variability [34] as well as a reduction in maternal depression and anxiety [35]. Studies investigating the use of specific oils in massage versus no oil suggest improved weight gain [3638]. Overall the evidence remains weak, mainly due to small sample sizes, heterogeneity and poor methodology in some studies.…”
Section: Introductionmentioning
confidence: 99%
“…A series of small hospital-based studies have demonstrated that topical applications of vegetable oils can improve thermoregulation, 68,69 skin condition, 70,71 and serum-essential fatty acid profiles, 69,72 correct essential fatty acid deficiency, 73 and increase weight and length gain. [74][75][76][77] Importantly, two hospital-based trials of preterm babies massaged with high-linoleic acid sunflower seed oil 70,77,78 have demonstrated reductions in nosocomial infections and mortality within 28 days. A recent trial of oil massage of preterm infants with coconut oil has produced similar results.…”
Section: Topical Emollient Therapymentioning
confidence: 99%